Oral hygiene knowledge and practices among mothers of 3- to 6-Year-old preschool children visiting anganwadis of Bangalore City - Vasuda Rajanna; Sanjeev Khanagar; S Naganandini (Wolters Kluwer Medknow Publications, 2019)
Background: Children under the age of 6 years spend most of their time with their parents and guardians, especially mothers, even when they attend preschool or nurseries. It has been found that young children's oral health maintenance and outcomes are influenced by their parent's knowledge and beliefs. Mothers play a vital role in maintaining their children's oral hygiene. Aim: The aim of this study was done to assess the knowledge and practice of oral hygiene among mothers of 3- to 6-year-old preschool children visiting the anganwadis of Bangalore city. Materials and Methods: Mothers of children aged 3-6 years visiting various anganwadis were invited to participate in the study. The sample comprised of 200 mothers through simple random sampling. A pretested questionnaire covering sociodemographic details, importance of brushing deciduous teeth, and oral hygiene practices was distributed to mothers who were willing to participate. Results: In the present study, majority of mothers visiting the anganwadi had only primary school education (79%). About 79.4% of mothers did not have any knowledge regarding the time of eruption of their child's deciduous teeth, 63.8% of mothers did not know the importance of brushing their child's deciduous teeth, and 84.3% mothers did not know that oral diseases can affect general health. Conclusion: The result of the present study showed that the oral health knowledge among the mothers visiting the anganwadis was poor. Awareness programs targeting expectant mothers visiting anganwadis should be employed by training the anganwadi teachers, and importance of primary teeth should be emphasized in different oral health education programs